A Note on sustainable use of Himalayan Birch (Betula utilis D. Don) by Local Tribal Community of Sechu-Tuan Nalla Wildlife Sanctuary, Chamba, Himachal Pradesh - Kumar, Puneet; Singh, Harminder; Ambrish, Kumar (Indian Forester, 2018)
No Abstract.